Efficacy of neoadjuvant chemotherapy in male breast cancer compared with female breast cancer. Issue 21 (7th September 2022) - Leone, José Pablo; Hassett, Michael J.; Leone, Julieta; Tolaney, Sara M.; Vallejo, Carlos T.; Leone, Bernardo A.; Winer, Eric P.; Lin, Nancy U.
Abstract : Background: Neoadjuvant chemotherapy (NAC) is standard for many females with breast cancer (FBC). The efficacy of NAC in male breast cancer (MaBC) is unclear. The aim of this study was to compare proportions of pathologic complete response (pCR) between MaBC and FBC by tumor subtype (TS). Methods: MaBC and FBC treated with NAC between 2010 and 2016, with known TS, were evaluated from the National Cancer Database. Proportions of pCR (ypT0/Tis ypN0) were compared between sexes within TS by Fisher test. Multivariable logistic regression assessed the independent association of sex with pCR. Overall survival (OS) was estimated by Kaplan–Meier. Results: A total of 385 MaBC and 68, 065 FBC were included. Median time from initiation of NAC to surgery was 143 days in MaBC and 148 days in FBC. Proportions of pCR in MaBC and FBC by TS were: hormone receptor–positive/human epidermal growth factor receptor 2–negative (HR+/HER2–): 4.9% vs 9.7%, p  = .01; HR+/HER2+: 16.1% vs 33.6%, p  < .001; HR–/HER2+: 44.0% vs 53.2%, p  = .42; and HR–/HER2–: 21.4% vs 32.1%, p  = .18, respectively. FBC had twice the odds of pCR than MaBC (adjusted odds ratio, 2.0; 95% CI, 1.5–2.8; p  < .001). Five‐year OS for MaBC with pCR vs not was 90% vs 64.7%; p  = .02. Five‐year OS for FBC with pCR vs not was 91.9% vs 75.3%; p  < .01. Conclusions: Proportions and odds of pCR to NAC were numerically lower in MaBC compared with FBC for each TS and statistically significant for HR+/HER2– and HR+/HER2+. The independent association of sex with pCR was confirmed in multivariable analysis. pCR is prognostic in both MaBC and FBC. Abstract : Using the National Cancer Database, the authors show that the proportions of pathologic complete response (pCR) following neoadjuvant chemotherapy by tumor subtype in breast cancer were uniformly lower in men compared with women. pCR may serve as an endpoint for clinical trials in men with certain breast cancer subtypes and facilitate the identification of more effective therapies using smaller sample sizes.